Multiple Polypoid Lesions in the Colon: What Is Your Diagnosis? - Hakan Ümit Ünal; Alper Tunga Canpolat; Ali Türk; Murat Saruç (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Ünal HÜ, Canpolat AT, Türk A, Saruç M. Multiple polypoid lesions in the colon: What is your diagnosis? Turk J Gastroenterol. 2022;33(8):720-721.